THE ROLE OF DIGITAL MEDIA IN SHAPING CONTEMPORARY SOCIAL MOVEMENTS (Eureka Journal of Humanities and Social Research, 2025)
This study explores the transformative influence of digital media on contemporary social movements, emphasizing how online platforms shape collective identity, mobilization strategies, and policy impact. Using case studies of global campaigns like Fridays for Future and #MeToo, the research highlights the dual role of social media as both a democratic enabler and a polarizing agent. Findings reveal that digital media has enhanced inclusivity and reach while introducing challenges related to misinformation and activism fatigue.
Keywords: Digital activism, social movements, online mobilization, social media, collective identity